PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA KARYAWAN BIRO PERJALANAN WISATA DI KOTA DENPASAR - Mayanti Dewi, Putu; Parta, I Nyoman (CV. Lafadz Jaya, 2024)
The purpose of this study was to determine the effect of motivation and job satisfaction on the performance of Travel Bureau employees in Denpasar City, as well as the role of job satisfaction as a mediating variable on the effect of motivation on employee performance. This type of research includes quantitative research. The population is all employees of the Travel Bureau in Denpasar City, while the research sample is 100 people. The sampling technique uses purposive random sampling. Retrieval of data using a questionnaire. The analytical method uses descriptive analysis and path analysis to test the research hypothesis. The conclusion of the research shows that motivation has an effect on employee job satisfaction, job satisfaction has an effect on employee performance, work motivation has an effect on employee performance, and work motivation has an indirect effect on employee performance through job satisfaction.